Potent priming by inactivated whole influenza virus particle vaccines is linked to viral RNA uptake into antigen presenting cells. Issue 29 (29th June 2021) - Shingai, Masashi; Nomura, Naoki; Sekiya, Toshiki; Ohno, Marumi; Fujikura, Daisuke; Handabile, Chimuka; Omori, Ryosuke; Ohara, Yuki; Nishimura, Tomohiro; Endo, Masafumi; Kimachi, Kazuhiko; Mitsumata, Ryotarou; et al.
Abstract: Current detergent or ether-disrupted split vaccines (SVs) for influenza do not always induce adequate immune responses, especially in young children. This contrasts with the whole virus particle vaccines (WPVs) originally used against influenza that were immunogenic in both adults and children but were replaced by SV in the 1970s due to concerns with reactogenicity. In this study, we re-evaluated the immunogenicity of WPV and SV, prepared from the same batch of purified influenza virus, in cynomolgus macaques and confirmed that WPV is superior to SV in priming potency. In addition, we compared the ability of WPV and SV to induce innate immune responses, including the maturation of dendritic cells (DCs) in vitro . WPV stimulated greater production of inflammatory cytokines and type-I interferon in immune cells from mice and macaques compared to SV. Since these innate responses are likely triggered by the activation of pattern recognition receptors (PRRs) by viral RNA, the quantity and quality of viral RNA in each vaccine were assessed. Although the quantity of viral RNA was similar in the two vaccines, the amount of viral RNA of a length that can be recognized by PRRs was over 100-fold greater in WPV than in SV. More importantly, 1000-fold more viral RNA was delivered to DCs by WPV than by SV when exposed to preparations containing the same amount of HA protein. Furthermore, WPV induced up-regulation of the DC maturation marker CD86 on murine DCs, while SV did not. The present results suggest that the activation of antigen-presenting DCs, by PRR-recognizable viral RNA contained in WPV is responsible for the effective priming potency of WPV observed in naïve mice and macaques. WPV is thus recommended as an alternative option for seasonal influenza vaccines, especially for children.